ANALYSIS OF LEARNING EVALUATION THROUGH STUDENTS’ DRAMA TEXT WRITING IN SENIOR HIGH SCHOOL - Amaliavanti, Zhafirah (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Evaluation of drama text learning in secondary schools is often conducted intuitively, without a systematic guideline, despite the fact that students’ written works can reflect comprehensive learning outcomes. This study aims to evaluate the results of drama text learning through an analysis of students’ scripts and to formulate assessment principles in the form of an applicable rubric for teachers. A descriptive qualitative method was employed, using documentation and content analysis techniques on nine drama texts written by eleventh-grade students. The findings reveal variations in students’ achievements across five key aspects: dramatic structure, characterization, dialogue, language and emotion, as well as values or messages. Based on these findings, an authentic assessment rubric was developed to support formative and contextual evaluation. This rubric is expected to assist teachers in conducting fairer and more structured assessments of student literary works in alignment with curriculum demands. Further research is recommended to explore students’ writing processes and reflective thinking in greater depth.